Food Safety Assessment of Genetically Modified Crops (International Journal of Food and Nutritional Sciences, 2022)
The evaluation of food safety in genetically modified (GM) crops is a critical area inagricultural biotechnology. This paper presents a novel approach using effective deep learningtechniques for the assessment of GM crops' safety.